The Global Political Economy of Israel - Jonathan Nitzan; Shimshon Bichler (Pluto Press, 2002)
Over the past century, Israel has been transformed from an agricultural colony, to a welfare-warfare state, to a globally integrated “market economy” characterised by great income disparities. What lies behind this transformation? Why the shift in emphasis from “war profits” to “peace dividends” – and back to conflict? How did egalitarianism give rise to inequality? Who are the big winners here, and how have they shaped their world? Never before have these questions been answered as they are in this highly original book. In order to understand capitalist development, argue Bichler and Nitzan, we need to break the artificial separation between “economics” and “politics”, and think of accumulation itself as “capitalisation of power”. Applying this concept to Israel, and drawing on seemingly unrelated phenomena, the authors reveal the big picture that never makes it to the news. Diverse processes – such as global accumulation cycles, regional conflicts and energy crises, ruling class formation and dominant ideology, militarism and dependency, inflation and recession, the politics of high-technology and the transnationalisation of ownership – are all woven into a single story. The result is a fascinating account of one of the world”s most volatile regions, and a new way of understanding the global political economy.
Keywords: 330; arms; accumulation; acquisitions; capital; capitalism; centralization; competition; conflict; conglomeration; corporation; credit; crisis; debt; demographics; development; distribution; dual economy; elite; energy; finance; globalization; growth; imperialism; distribution; inflation; institutionalism; IPE; Israel; labour; liberalization; M&A; merger; methodology; Middle East; military; national interest; security; oil; OPEC; ownership; Palestine; peace; politics; power; privatization; profit; ruling class; sabotage; stagflation; state; stock market; technology; TNC; United States; US; violence; war; Zionism